Studi Analisis Pengaruh Temperatur Terhadap Ketebalan Pada Proses Pengeringan Ubi Gaplek - Ozi Alvindo; Roni Novison (Jurnal Teknik Mesin, 2022)
This analytical study aims to determine the effect of temperature on the thickness of cassava pieces. This test has 3 parameters, namely 3 variations in the thickness of cassava pieces (3 mm, 4 mm, 5 mm), 3 variations in drying temperature (40 °C, 60 °C, 80 °C), and 3 variations in drying time (120 minutes, 240 minutes and 360 minutes) using a dry cassava cassava oven and using a heat source from 2 heaters with a power of 800 Watt. The Drying Oven used has 3 shelves, each rack has a capacity of 5.76 kg in one drying. This research shows that the best parameters for drying cassava with a capacity of 500 g are 3 mm, 80 °C, 240 minutes and the second parameter is 3 mm, 60 °C, 360 minutes. The results of the parameters of 3 mm, 80 °C, 240 minutes with an initial weight of 500 gr using a heater were able to make the initial water content of sweet potatoes from 32.175% to 6.708%. The results of the thickness parameters of 3 mm, 60 °C, 360 minutes using a heater were able to make the initial water content of sweet potatoes from 32.175% to 7.20%. The results of the parameters 3 mm, 60 °C, 360 minutes were able to make the initial water content of sweet potatoes from 32.175% to 5.23%. The Taguchi method was used for the experiment. The results of this study indicate that during the drying process the air changes process, and changes in weight on the sweet potato pieces. The higher the temperature and the longer the drying time, the lower the water content along with the increase in cassava pieces